Effect of membrane fusion protein AdeT1 on the antimicrobial resistance of Escherichia coli - Barlow, Victoria L.; Lai, Shu-Jung; Chen, Chia-Yu; Tsai, Cheng-Han; Wu, Shih-Hsiung; Tsai, Yu-Hsuan (Scientific reports, 2020)
Acinetobacter baumannii is a prevalent pathogen that can rapidly acquire resistance to antibiotics. Indeed, multidrug-resistant A. baumannii is a major cause of hospital-acquired infections and has been recognised by the World Health Organization as one of the most threatening bacteria to our society. Resistance-nodulation-division (RND) type multidrug efflux pumps have been demonstrated to convey antibiotic resistance to a wide range of pathogens and are the primary resistance mechanism employed by A. baumannii . A component of an RND pump in A. baumannii, AdeT1, was previously demonstrated to enhance the antimicrobial resistance of Escherichia coli . Here, we report the results of experiments which demonstrate that wild-type AdeT1 does not confer antimicrobial resistance in E. coli , highlighting the importance of verifying protein production when determining minimum inhibitory concentrations (MICs) especially by broth dilution. Nevertheless, using an agar-based MIC assay, we found that propionylation of Lys280 on AdeT1 renders E. coli cells more resistant to erythromycin.